2001
DOI: 10.1021/es001459w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical and Biological Factors on Trophic Transfer of Persistent Organic Pollutants in the Northwater Polynya Marine Food Web

Abstract: Persistent organic pollutants (POPs) and stable isotopes of nitrogen (delta 15N) were measured in zooplankton (6 species), a benthic invertebrate (Anonyx nugax), Arctic cod (Boreogadus saida), seabirds (6 species), and ringed seals (Phoca hispida) collected in 1998 in the Northwater Polynya to examine effects of biological and chemical factors on trophic transfer of POPs in an Arctic marine food web. Strong positive relationships were found between recalcitrant POP concentrations (lipid corrected) and trophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
500
8
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 627 publications
(551 citation statements)
references
References 38 publications
37
500
8
6
Order By: Relevance
“…e DDTs is p,p′-DDE, p,p′-DDD, and p,p′-DDT for zooplankton and fish; p,p′-DDE for seabirds; and p,p′-DDE and p,p′-DDT for seals. and the recoveries were within acceptable ranges as described in previous publications (9,10,14,15,24,25,27).…”
Section: Marine Mammalssupporting
confidence: 76%
See 1 more Smart Citation
“…e DDTs is p,p′-DDE, p,p′-DDD, and p,p′-DDT for zooplankton and fish; p,p′-DDE for seabirds; and p,p′-DDE and p,p′-DDT for seals. and the recoveries were within acceptable ranges as described in previous publications (9,10,14,15,24,25,27).…”
Section: Marine Mammalssupporting
confidence: 76%
“…Methods with modifications for extraction, cleanup, separation, identification, and quantification followed standard procedures and are described in previous publications (9,10,14,15,24,25,27). The participating laboratories' analytical quality has been confirmed by good results from international intercalibration tests (9,24). All NOW and CBS samples were analyzed on high-resolution gas chromatograph equipped with Ni-electron capture detector, except NOW ringed seals for which the gas chromatograph was equipped with a mass spectrometer detector.…”
Section: Methodsmentioning
confidence: 99%
“…Because each contaminant (or group of summed contaminants) is biomagnified to a different extent, contaminant ratios will also change as contaminants from prey are assimilated by the predator (Fisk et al, 2001;Hoekstra et al, 2003). However, biomagnification factors (BMFs) appear to be species-specific (Fisk et al, 2001;Hoekstra et al, 2003) and no BMFs have been reported for killer whales.…”
Section: Discussionmentioning
confidence: 99%
“…Devido à toxicidade dos compostos, baixa degradação nas águas e fatores de bioacumulação (que eleva exponencialmente a contaminação em seres vivos devido à acumulação em tecidos adiposos), seres vivos expostos às águas contaminadas podem contaminar toda a cadeia alimentar, com níveis prejudiciais [12][13][14][15][16][17][18][19] . A simulação apontou que em 500 anos o meio ambiente não estará livre da contaminação por mirex e clordecona, devido à retenção dos poluentes no solo.…”
Section: Resultsunclassified